Respostas
respondido por:
1
12X2 - 9X -12X +9= 2 - 3X - 3
12X2 + 3x -12X = 2 - 3 - 9
12X2 - 9X = - 10
(os números após a letra são expoentes)
12X2 + 3x -12X = 2 - 3 - 9
12X2 - 9X = - 10
(os números após a letra são expoentes)
respondido por:
1
Resposta:
3x -12x + 9 = 2 -3x +3
-3x = -6 (multiplica por -1)
3x = 6
x = 2
;)
3x -12x + 9 = 2 -3x +3
-3x = -6 (multiplica por -1)
3x = 6
x = 2
;)
juliathaisa:
✌✌
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás